Pengaruh Self Efficacy Terhadap Kinerja Ikm Kulit Di Kabupaten Magetan Yang Dimediasi Oleh Resiiensi - Anggun Dyan Kartika Rini; Andre Dwijanto Witjaksono; Anang Kistyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The impact of large-scale national restrictions of Covid-19 pandemic to other sectorss in the world is especially in the economic sector. Indonesia dominated by MSMEs which is it be a backbone of national’s economy in Indonesia. That’s way, MSMEs business person required to be able to adapt on pandemic’s situationin order to maintain and increase corporation to continuity of business sustainability. In other impact of the pandemic happrned is the increasing of product imported, online shipping and the products produces are less fashionable. This research purpose to analyze the influence of self efficacy on tke IKM leather’s performance in Magetan which mediated by resilience. This research is quantitative, with respondents of IKM’s leather in Magetan who still surviving after Covid-19 pandemic. Data obtained from 138 respondents and it was processed using SEM regression analysis with SEM PLS analysis tools. The results of this research showed that the Self Efficacy’s variable has a significant effect on the IKM leather’s performance in Magetan which mediated by resilience.